2002
DOI: 10.1095/biolreprod66.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Follicular Development to Produce Developmentally Competent Bovine Oocytes1

Abstract: Superstimulation in donor cows increases the number of cumulus-oocyte complexes (COC), but when compared to in vivo maturation, in vitro maturation results in only half as many blastocysts after prolonged in vitro culture. The objective of this study was to establish a superstimulation protocol that would produce a maximal number of competent COC for standard in vitro embryo production. During experiment 1, eight cyclic Holstein heifers were superstimulated with four doses of FSH. Half the heifers received an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
135
3
18

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(164 citation statements)
references
References 34 publications
8
135
3
18
Order By: Relevance
“…In parallel, we and others have observed that granulosa/follicular gene expression may be associated with developmental competence of the enclosed oocyte in bovines (Robert et al 2001), rats (Jiang et al 2010), and humans (Assidi et al 2008, 2010, 2010. In our previous experiment, it was observed that an improved developmental rate was obtained with a hormonal treatment consisting of 3 days of stimulation using FSH plus a coasting period of 44 h (Blondin et al 2002).…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…In parallel, we and others have observed that granulosa/follicular gene expression may be associated with developmental competence of the enclosed oocyte in bovines (Robert et al 2001), rats (Jiang et al 2010), and humans (Assidi et al 2008, 2010, 2010. In our previous experiment, it was observed that an improved developmental rate was obtained with a hormonal treatment consisting of 3 days of stimulation using FSH plus a coasting period of 44 h (Blondin et al 2002).…”
Section: Introductionsupporting
confidence: 51%
“…In cattle, the follicle status has a significant effect on oocyte quality, and through several protocols, it has been demonstrated that hormonal pretreatment of ovaries with gonadotropins can improve oocyte quality in a time-regulated manner (Blondin et al 1996(Blondin et al , 1997(Blondin et al , 2002. In parallel, we and others have observed that granulosa/follicular gene expression may be associated with developmental competence of the enclosed oocyte in bovines (Robert et al 2001), rats (Jiang et al 2010), and humans (Assidi et al 2008, 2010, 2010.…”
Section: Introductionmentioning
confidence: 75%
“…Gonadotrophins such as FSH either alone (Bousquet et al 1999, Goodhand et al 1999, Sirard et al 1999 or in combination with LH (Blondin et al 2002, see a review by Merton et al 2003) and pregnant mare serum gonadotrophin (Pieterse et al 1991) have been used to improve the outcome of OPU in adult donor cows. Oocytes from superovulated cows are developmentally more competent than their non-stimulated counterparts (Faber et al 2003, Merton et al 2003, and specific changes in superovulatory treatment can greatly increase developmental competence of the oocyte (Blondin et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes from superovulated cows are developmentally more competent than their non-stimulated counterparts (Faber et al 2003, Merton et al 2003, and specific changes in superovulatory treatment can greatly increase developmental competence of the oocyte (Blondin et al 2002). However, due to high variability among gonadotrophin batches and being an animal product we considered ROH as a potential Table 6 Embryonic development of oocytes obtained during sessions 1 to 5 from cows treated with all-trans retinol (ROH) or corn oil (vehicle) and matured with or without 9-cis retinoic acid (RA).…”
Section: Discussionmentioning
confidence: 99%
“…However, developmental competence of oocytes is acquired through completion of both nuclear and cytoplasmic maturation. Only a small portion of in vitro-matured oocytes go on to develop into blastocysts, whereas oocytes matured in vivo have much higher embryo development rates (Van de Leemput et al 1999, Blondin et al 2002. Low blastocyst formation by in vitromatured oocytes indicates that current oocyte maturation systems do not adequately support either nuclear and/or cytoplasmic maturation.…”
Section: Introductionmentioning
confidence: 99%